COVERAGE OF CITY LIFE DURING THE OCCUPATION OF KHERSON IN 2022 IN ORAL HISTORICAL REFERENCES (Південний архів (історичні науки), 2023)
The purpose of the study is to characterize and analyze the peculiarities of the organization of living conditions under occupation during the full-scale Russian aggression in March-November 2022 on the example of Kherson. The methodological basis of the study was based on such methods as oral history and observation. Oral history is the main methodological basis, as it is a powerful tool for understanding the organization of people’s lives in the process of fundamental civilizational transformations. The main results of the study. The main task of the author is to reveal the peculiarities of the organization of living conditions in urban space under the “Kherson model of occupation” and to present an inside view of the processes that took place during the temporary occupation of the city. The main source used is the documented stories of Kherson residents of different ages and social backgrounds. The study attempts to understand and outline the peculiarities of Kherson’s stay under occupation at the everyday level, which affected the organization of everyday life and the civilian population’s personal experience of life/survival. The work is complemented by various stories about the endurance of the temporary occupation by the local population, both on the basis of oral history and on the basis of reflection on their personal stay in the occupied zone. The article draws attention to the experience of local residents, including the organization of life and work, participation in civil resistance, rejection of the Russian occupation, mutual assistance and support. Conclusions. The conclusions summarize the occupation reality in which the city’s residents found themselves. It became a special atmosphere in which ways of organizing life/survival, confrontation/ struggle, expectations of liberation/preservation of national identity were formed. In this atmosphere, freedom was nurtured, value beliefs were strengthened, and Ukrainian identity was cemented.
Keywords: Southern Ukraine, Kherson, occupation, socio-economic relations, large-scale Russian-Ukrainian war, everyday life